Routing technology based on virtualization software-defined networking concept - Kravchenko, Yu.V.; Herasymenko, K.V.; Starkova, O.V.; Bulgakova, A.Y. (PROBLEMS IN PROGRAMMING, 2024)
One of the main characteristics of the digital revolution is the acceleration of change. The technologies that have fueled the digital revolution over the past decades are experiencing increasingly rapid innovation cycles. For today, a substantial growth of amount of users, devices, applications and traffic has presented new challenges to service providers. The SDN paradigm emerged to address some of these emerging challenges. SDN simplifies network management and allows automated network configuration on demand with optimal use of network resources. The work is devoted to the present networks research and the identification of opportunities for the implementation of virtualization of network functions in the context of SDN and NFV concepts. Because these are two new technological trends that are transforming network management. Together, they simplify the provisioning of network resources and provide greater network flexibility.Prombles in programming 2024; 2-3: 343-350